2012
DOI: 10.1002/ccd.23470
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous interventions in high‐risk patients following mustard repair of transposition of the great arteries

Abstract: ObjectivesTo assess safety, efficacy, and intermediate term outcomes of percutaneous interventions in Mustard patients.BackgroundBaffle leaks and obstruction are present in 20% of Mustard survivors. Surgical reintervention is associated with high mortality.MethodsRetrospective review of percutaneous interventions performed at three adult congenital catheterization programs.ResultsOverall, 26 catheterizations and 29 interventions were performed in 22 patients (mean age 32.4 ± 8.3 years). Previous laser pacemake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Modern treatment options include intravascular stenting or surgical revision . Hill et al reported a multicenter case series including 19 patients who had undergone successful percutaneous stent implantation of systemic venous baffle obstructions with mid‐term follow‐up data . The largest single center series to describe baffle intervention included 24 patients who underwent either stent implantation or balloon dilatation alone of only the superior vena cava baffle .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Modern treatment options include intravascular stenting or surgical revision . Hill et al reported a multicenter case series including 19 patients who had undergone successful percutaneous stent implantation of systemic venous baffle obstructions with mid‐term follow‐up data . The largest single center series to describe baffle intervention included 24 patients who underwent either stent implantation or balloon dilatation alone of only the superior vena cava baffle .…”
Section: Introductionsupporting
confidence: 61%
“…Perioperative mortality in patients referred for surgical baffle revision has been reported to be 36% . Modern treatment options include intravascular stenting or surgical revision . Hill et al reported a multicenter case series including 19 patients who had undergone successful percutaneous stent implantation of systemic venous baffle obstructions with mid‐term follow‐up data .…”
Section: Introductionmentioning
confidence: 99%
“…[2236] Two case series have more recently demonstrated good short and medium-term outcomes with these procedures. [37,38] The first case series came out of Germany, where 12 of 13 patients with a median age of 20.8 years underwent 14 successful procedures including baffle stent and septal occluder placement without complication, baffle rupture, or hemorrhage. In this group, at 21 months of follow-up there was no recurrent stenosis or leak.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that stent placement for baffle obstruction is effective and likely safer than surgical intervention, and baffle leak occlusion is safely treated from a percutaneous approach, albeit the presence of residual leak in the short-term. [38]. …”
Section: Discussionmentioning
confidence: 99%
“…For some patients, relief of baffle leaks and/or stenosis can translate to significant improvements in functional class and hemodynamics. 11 Percutaneous interventions include balloon angioplasty for baffle stenosis with or without stent placement. Baffle leaks can also be treated with deployment of a covered stent.…”
Section: Invasive Hemodynamic Evaluation and Transcatheter Interventimentioning
confidence: 99%